Effect of polka raspberry (Rubus idaeus L.) extract on corrosion inhibition of bronze - Farzet Bikić; Fehim Korać (Zaštita Materijala)
Plant extracts contain a large number of organic compounds, and one of the large groups of compounds present are phenolic compounds. Researchers have shown that a certain number of these compounds can be used as effective metal corrosion inhibitors. Plant extracts of raspberries (leaves, flowers, and fruit) were obtained by ultrasonic extraction using 96% ethanol as a solvent. The UV/Vis spectrophotometric method was used to determine the content of total phenols in plant extracts. Phenolic acids and flavonoids in plant extracts were separated and quantified using the HPLC method. Tafel extrapolation was used for electrochemical characteristics. The corrosion characteristics and behavior of bronze in 3% NaCl solution, with and without the presence of plant extracts were investigated. The content of total phenols in leaves was found to be 107.14±3.63 mg/g in flowers 148.99±9.02 mg/g and in fruits was 8.75±0.61 mg/g. Leaf extract in a concentration of 0.04828 g/L according to the Tafel extrapolation method provides the best protection for bronze in a 3% NaCl solution. The same concentration in the case of flower and fruit extracts proved to be the most favorable.